Electronic transport study for SF6 Plasma - A I Ahmed; N A Hamdoon (Tikrit Journal of Pure Science)
Determination the electron transport parameters, (drift velocity ( ) , mean electron energy ( ), diffusion coefficient (D), mobility ( ) and ionization coefficient ( ) ), in an attempt to show the influence of the presence of dust on their behavior in a direct current low pressure SF6 glow discharge .The Boltzmann Transport Equation (BTE), using two-term approximation are solved self-consistly. Making use of simulation model program for the numerical finite element method (FEM) of the boltzman equation to calculate the electron energy distribution function and the transport parameters in the range of reduced electric field  E/N (300_1000 Td). As well as evaluated the electron temperature in pristine and dusty plasma and dust surface potential at E/N (40 Td) .